Pelatihan Penulisan Artikel Ilmiah Guna Membangun Budaya Literasi Sains Bagi Guru Sekolah Dasar - Dinda Rahma Dewi; M. Zuhnir Piliang; Mutia Meireni; Abdul Rahman Alfarasyi; Hayatul Khairul Rahmat (Indonesian Journal of Emerging Trends in Community Empowerment, 2023)
Community service activities in the form of scientific article writing training for teachers at SDIT Nuur A'laa Nuur Tambun, Bekasi aim to increase understanding and awareness of the benefits of writing scientific articles to build a culture of scientific literacy at SDIT Nuur A'laa Nuur Tambun, Bekasi. The method applied to this community service activity is a variety of lectures and questions and answers. This training is expected to be a good start in developing teacher writing competence and a culture of scientific literacy in educational institutions. This scientific article writing training activity was quite successful as can be seen from the number of participants who were interested and understood the material by 50%. To maximize further evaluation, it is hoped that face-to-face training and full assistance for each participant will be carried out.